The Translation and Factor Structure of the Inventory for Parent and Peer Attachment- Revised (IPPA-R) - Munir, Aasma; Malik, Jamil Ahmed; Abbas, Ghulam (Journal of Pakistan Psychiatric Society, 2020)
Objective. Among the measures of attachment, which focus on individual differences specifically in adolescents and stress on the strength of their relationships with parents and peers, the inventory for parent and peer attachment is found to be most reliable and widely used measure of attachment but the factor structure of the inventory call for further exploration and cultural validation. The objective of the present study was two folded: First, to translate the Inventory in Urdu language. Secondly, to test the construct validity of latest version of IPPA-R by using Confirmatory Factor Analysis and to evaluate the psychometric properties of resulting factor. Method. Participants of the study were 706 Pakistani adolescents. Three models were compared which are debated in the literature: the uni-factor model (attachment security), the two-factor model (trust–communication and alienation) and the three-factor model (trust, communication and alienation). Results. Our results suggest good reliability of the latest version (IPPA-R). Factor analysis showed that the two-factor model had the best fit. Two factor models across gender also presented an excellent fit suggesting generalizability of inventory for both boys and girls. Conclusion. The availability of indigenously validated inventory for parent and peer attachment in Urdu language is expected to facilitate the assessment of adolescent’s parent and peer attachment in Pakistani population.